1996
DOI: 10.3109/01485019608988508
|View full text |Cite
|
Sign up to set email alerts
|

Chronobiological Fluctuations in Semen Parameters with a Constant Abstinence Period

Abstract: This study examined the seasonal variation in three semen parameters (total sperm count, % grade a progressive motility and sperm morphology according to strict criteria) with an identical abstinence period of 24 h. A total of 340 spermiograms of 107 different men enrolled in an intrauterine insemination (IUI) program were examined. To reduce variation due to interindividual disparities in semen quality, differences of each test result from the mean value obtained for that individual were analyzed. Mean values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 29 publications
0
20
0
Order By: Relevance
“…In humans, the effect of season rotation on sperm parameters is still controversial. Several studies confirmed a seasonal pattern of sperm variations (Andolz et al, 2001;Chen et al, 2004), whereas others did not (Menge and Beitner, 1989;Ombelet et al, 1996). The finding of seasonal change of chromatin condensation in human sperms seems to confirm this hypothesis (Henkel et al, 2001;Snyder, 1990).…”
Section: Discussionmentioning
confidence: 64%
“…In humans, the effect of season rotation on sperm parameters is still controversial. Several studies confirmed a seasonal pattern of sperm variations (Andolz et al, 2001;Chen et al, 2004), whereas others did not (Menge and Beitner, 1989;Ombelet et al, 1996). The finding of seasonal change of chromatin condensation in human sperms seems to confirm this hypothesis (Henkel et al, 2001;Snyder, 1990).…”
Section: Discussionmentioning
confidence: 64%
“…With regard to sperm concentration and sperm motility and vitality, contradictory results have been published. While Mortimer et al (1983) and Ombelet et al (1996) could not find significant seasonal variations of these parameters, others clearly emphasize such an effect (Tjoa et al, 1982;Politoff et al, 1989;Saint Pol et al, 1989;Centola and Eberly, 1999;Andolz et al, 2001;Henkel et al, 2001). Seasonal variations in sperm concentration were clearly not attributable to differences in sexual abstinence (Gyllenborg et al, 1999).…”
Section: Discussionmentioning
confidence: 97%
“…Besides, semen quality is affected by several factors such as abstinence duration, frequency of ejaculate, fibril illness, general health, infection of genital tracts, urogenital surgery and the environment (Freund ; Baker et al ., ; Ombelet et al ., ; Carlsen et al ., , ; De Jonge et al ., ). One of the first studies to report on the effect of abstinence on sperm quality after specified target days of abstinence in humans showed that sperm numbers and semen volume increased with duration of abstinence.…”
Section: Discussionmentioning
confidence: 99%